A Simple Formula to Estimate Electron Mobility in a MOSFET - Chanana, Ravi Kumar (European Journal of Applied Sciences, 2024)
This research communication gives a simple formula to estimate electron mobility in a metal-oxide-semiconductor field-effect-transistor (MOSFET). The example semiconductor chosen is the 4H-polytype of the Silicon Carbide, oriented in two faces of (0001) and (1120). The MOSFETs fabricated on these epi-surfaces have dry thermally grown amorphous silicon dioxide. The semiconductor/oxide interface is annealed in nitric oxide (NO) to incorporate Nitrogen only at the interface that passivates the interface traps to give higher channel mobility. The estimated mobility is presented in Table 1.